The Investigation of First Year University Students’ Online Self-Directed Readiness Level - Yeyisani Evans Makhubele (Journal of Education and Teaching, 2024)
This study aims to investigate the online learning readiness of first year students at the University of Mpumalanga in South Africa. This university uses Moodle as its online Learning Management System. This is a quantitative, non-experimental study within a positivism paradigm. 150 students were randomly sampled and were enrolled for a Diploma in Agriculture programmed. A Self-Directed Learning Readiness Scale (SDLRS) questionnaire was used to measure the readiness level for students’ SDL. The results reveal that more than two-thirds of the students have a medium self-directed readiness level with a total mean for all the questions of 2.91, a standard deviation of 0.79, and a variance of 0.77. This shows that first-year students are therefore not self-directed learners, which makes the transition to tertiary education difficult. This study is useful because assessing the level of readiness towards SDL among first year university students could help to introduce the modern method of student-centered teaching approach. The results of this study could assist universities to develop intervention strategies that will encourage self-directed learning.